Inheritance and Establishment of Gut Microbiota in Chickens - Ding, Jinmei; Dai, Ronghua; Yang, Lingyu; He, Chuan; Xu, Ke; Liu, Shuyun; Zhao, Wenjing; Xiao, Lu; Luo, Lingxiao; Zhang, Yan; Meng, He (Frontiers in Microbiology, 2017)
In mammals, the microbiota can be transmitted from the placenta, uterus, and vagina of the mother to the infant. Unlike mammals, development of the avian embryo is a process isolated from the mother and thus in the avian embryo the gut microbial developmental process remains elusive. To explore the establishment and inheritance of the gut microbiome in the avian embryo, we used the chicken as the model organism to investigate the gut microbial composition in embryos, chicks and maternal hens. We observed: (1) 28 phyla and 162 genera of microbes in embryos where the dominated genus was Halomonas (79%). (2) 65 genera were core microbiota in all stages with 42% and 62% gut microbial genera of embryo were found in maternal hen and chick, respectively. There was a moderate correlation (0.40) between the embryo and maternal, and 0.52 between the embryo and chick at the family level. (3) Gut microbes that are involved in substance metabolism, infectious disease, and environmental adaptation are enriched in embryos, chicks, and maternal hens, respectively. (4) 94% genera of gut microbial composition were similar among three different chicken breeds which were maintained under similar conditions. Our findings provide evidence to support the hypothesis that part of the microbial colonizers harbored in early embryos were inherited from maternal hens, and the gut microbial abundance and diversity were influenced by environmental factors and host genetic variation during development.